2006
DOI: 10.1111/j.1440-1681.2007.04543.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Landiolol on Mechanical and Metabolic Changes in Rat Reperfused Ischaemic Hearts

Abstract: 1. The aim of the present study was to clarify the effects of landiolol, a short-acting selective beta(1)-adrenoceptor blocking agent, on mechanical and metabolic changes in postischaemic perfused hearts. 2. Rat isolated hearts (n = 30) were randomly separated into non-ischaemic or ischaemic groups. The latter group was further divided into Krebs'-Henseleit solution (KHS)- and landiolol (30, 100 or 300 micromol/L)-treated groups. Ischaemic hearts were subjected to 25 min global ischaemia and 20 min reperfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Sakanashi et al [15] reported that landiolol at 300 lM ameliorated myocardial ischemiareperfusion injuries; in our study, the findings are similar to their reports.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Sakanashi et al [15] reported that landiolol at 300 lM ameliorated myocardial ischemiareperfusion injuries; in our study, the findings are similar to their reports.…”
Section: Discussionsupporting
confidence: 92%
“…Esmolol produced a dose-dependent decrease in mean arterial pressure that was not observed with landiolol [24]. Sakanashi et al [15] reported that, whereas 300 lM landiolol ameliorated myocardial dysfunction, LVEDP was similar to that in the ischemic KHS group. The effect of landiolol on postischemic cardiac parameters was said to be concentration dependent.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This is the key mechanism of cardioprotection by β-blockers. Other mechanisms of cardioprotection by β-blockers include the suppression of renin release [ 4 ], reduction of myocardial oxygen stress [ 5 ], and normalisation of calcium handling in the sarcoplasmic reticulum [ 6 ].…”
Section: Introductionmentioning
confidence: 99%